Fuzzy Boundaries: Review of Taxidermy and the Gothic: The Horror of Still Life (2024) by Elizabeth Effinger - Choudhury, Poulomi (Humanimalia, 2025)
Review of: Elizabeth Effinger, Taxidermy and the Gothic: The Horror of Still Life. Anthem Studies in Gothic Literature. London: Anthem Press, 2024. xliv + 172 pp. £80.00 (hb), £25.00 (ebook)